Loss of Inorganic Ions from Host Cells Infected with Chlamydia psittaci - Chang, George T. (1978)
Mouse fibroblasts (L cells) infected with the 6BC strain of Chlamydia psittaci released potassium ion (K(+)) into the extracellular milieu in a way that depended on size of inoculum and time after infection. When the multiplicity of infection was 500 to 1,000 50% infectious units (ID(50)) per L cell, loss of intracellular K(+) was first apparent 4 to 10 h after infection and was nearly complete at 6 to 20 h. Magnesium ion and inorganic phosphate (P(i)) were also released. Similar multiplicities of ultraviolet-inactivated C. psittaci also caused release of K(+). Leakage of inorganic ions probably resulted from immediate damage to the host-cell plasma membrane during ingestion of large numbers of chlamydiae. With multiplicities of 1 to 50 ID(50) per L cell, ingestion of C. psittaci was not by itself enough to cause release of K(+) and P(i) from infected L cells. There was a delay of 36 to 72 h between infection and massive leakage of intracellular ions during which time the chlamydiae multiplied extensively. Fifty ID(50) of ultraviolet-inactivated C. psittaci per L cell did not bring about significant leakage of K(+), even after 72 h. The mechanism whereby these multiplicities of infection destroy the ability of host cells to retain intracellular molecules is not known. HeLa 229 cells also released K(+) and P(i) after infection, but these losses occurred more slowly than in comparably infected L cells, possibly because C. psittaci did not multiply as extensively in HeLa cells as it did in L cells. The significance of the inability of chlamydiae-infected cells to regulate the flow of molecules through their plasma membranes is discussed.